International-legal regulation of socio-economic policy issues in the CIS - Belova, G.; Bazarova, G. (KSU publ., 2015)
In the scientific article discusses actual issues of international legal regulation of the socio-economic policy in the Commonwealth of Independent States. There is important role played by international law in an increasingly integration of states in determining the socio-economic policy. The article analyzes the main international legal instruments, which significantly affected at the socio-economic policy in the CIS and some problems with the implementation of international norms into national legislation.
Keywords: socio-economic policy; human rights; protection of socio-economic rights; UN; CIS; international pact